101 questions your brain has asked about itself but couldn't answer-- until now - Brynie, Faith Hickman, 1946- (Twenty-First Century Books, 2008)
Answers one hundred questions about the center of the human nervous system, covering brain chemistry, how the brain works, learning, memory, and "when things go wrong."